Gustave Roussy immune score is a prognostic marker in patients with small cell lung cancer undergoing immunotherapy: a real-world retrospective study - Shangguan, Jian; Huang, Xinyi; Liu, Xu; Zhang, Zengfu; Zhang, Xiaodong; Yu, Jinming; Chen, Dawei (Frontiers in Oncology, 2023)
Background: The utilization of the Gustave Roussy Immune Score (GRIm-Score) in patient selection for immunotherapy was initially reported. The objective of this retrospective study is to assess the potential of the GRIm-Score, a novel prognostic score based on nutritional and inflammatory markers, as a prognostic predictor in patients with small cell lung cancer (SCLC) undergoing immunotherapy. Methods: This retrospective study conducted at a single center included 159 patients with small cell lung cancer (SCLC) who received immune therapy. The objective of the study was to investigate potential differences in overall survival (OS) and progression-free survival (PFS) among patients stratified by their Gustave Roussy Immune Score (GRIm-Score), utilizing Kaplan-Meier survival analysis and the log-rank test. The final independent prognostic factors were identified through both propensity score matching (PSM) analysis and multivariable Cox-proportional hazards regression analysis. Results: Our analysis of the 159 patients revealed that there was a significant decrease in both overall survival (OS) and progression-free survival (PFS) with each increase in the Gustave Roussy Immune Score (GRIm-Score) group, displaying a stepwise pattern. Moreover, even after conducting propensity score matching (PSM) analysis, the significant associations between the modified 3-category risk scale-based GRIm-Score and survival outcomes remained significant. Both the total cohort and PSM cohort were subjected to multivariable analysis, which demonstrated that the three-category risk assessment-based GRIm-Score was a valuable predictor of both OS and PFS. Conclusions: In addition, the Gustave Roussy Immune Score (GRIm-Score) may serve as a valuable and non-invasive prognostic predictor for small cell lung cancer (SCLC) patients undergoing PD1/PD-L1 immunotherapy.